Comparison of Central Venous Catheter Related Deep Venous Thrombosis According to Insertion Site in an Intensive Care Unit of Bangladesh - Saha, Debasish Kumar; Nazneen, Suraiya; Ahsan, ASM Areef; Saha, Madhurima; Fatema, Kaniz; Ahmed, Fatema; Sultana, Rozina (Journal of Medicine, 2022)
Background: Central venous catheter (CVC) is usually inserted into subclavian, internal jugular, orfemoral vein in critically ill patients. CVCs are associated with intravascular (infectious, thrombotic) andmechanical complications. CVC related deep venous thrombosis (DVT) is a common intravascularcomplication.Objectives: To see the variation in occurrence of CVC related deep venous thrombosis according todifferent insertion site. Method: It was a prospective observational study conducted in dept. of Critical Care Medicine, BIRDEMGeneral Hospital; during a period of May, 2016 to July, 2019. Purposive sampling was conducted in patientsfulfilling the selection criteria. The CVCs were percutaneously inserted using the Seldinger techniquewith standard operating procedure. After CVC insertion, patients were followed up daily to see any signof deep venous thrombosis. After catheter removal [due to any cause including suspected catheterrelated blood stream infection (CRBSI), DVT, mechanical cause], all the study patients were investigated byduplex ultrasonography (USG) within 2 days for detection of venous thrombosis. The outcome wascatheter related deep venous thrombosis (DVT). Results: A total 349 patients, of which 167 (47.9%) patients had CVC in subclavian, 88 (25.2%) in internaljugular and 94 (26.9%) in femoral vein. Total 12 patients were suspected to have catheter related DVT, but11(3.2%) patients were confirmed as DVT by duplex USG. DVT occurred significantly higher in femoralcatheter site (8.5%) than subclavian (1.8%) and internal jugular site (0%). Conclusion: The occurrence of catheter related DVT was higher in femoral site than other two sites. J MEDICINE 2022; 23: 20-23